THE CRITICAL CONCEPT OF NORMAL PERSONALITY IN ISLAM - Abdul Hadi; Badrah Uyuni (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2021)
This study come to high light the normal personality in Islam in regarding to human nature and behaviors. human in the perception of Islam is composed of the body and spirit, and behavior. Is the outcome of the interaction of these two components, to understand that interaction and those relationships must be aware of the first part of the human, and the other part of God. Human behavior mostly belongs to two different systems, starting to work and influence since the creation of the fetus in the mother's womb, this creation has two aspects, one body and the other breathed the soul. The Islamic point of view in interpreting human behavior on several levels, each level is suitable for understanding a specific knowledge source and a specific research methodology: There is a reflexive level of behavior and could be understood by way of behavior theory. And there is a physiological level and is understood by the physiological path., and there is a social level and is understood by sociology and anthropology, and there is spiritual level and is understood by divine science (revelation). Studi ini menyoroti kepribadian normal dalam Islam dan kaitannya dengan sifat dan perilaku manusia. Manusia dalam persepsi Islam terdiri atas badan, roh, dan tingkah laku. Apakah interaksi dan hubungan komponen-komponen tersebut harus menyadari bagian pertama dari manusia, dan bagian lain dari Tuhan. Tingkah laku manusia sebagian besar termasuk dalam dua sistem yang berbeda, mulai dari bekerja dan terpengaruh sejak lahirnya janin dari kandungan ibu, ciptaan ini memiliki dua aspek, satunya adalah jasad dan satunya lagi adalah bernafas. Sudut pandang Islam dalam memaknai tingkah laku manusia terdiri dari beberapa tingkatan, masing-masing tingkatan cukup untuk memahami sumber pengetahuan tertentu dan metodologi penelitian tertentu: Ada tingkah laku yang bersifat refleksif dan dapat dipahami melalui teori tingkah laku. Dan ada tingkat fisiologis dan dipahami oleh jalur fisiologis., Dan ada tingkat sosial dan dipahami oleh ilmu sosiologi dan ilmu antropologi, dan ada tingkat spiritual dan dipahami oleh ilmu ketuhanan (wahyu).